(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The essay starts from the consideration that the new frontiers of the AI are forcing the jurist to rethink the fundamental categories of personal identity and identification. Today, these categories are characterised by greater fluidity and interchangeability: identification relies on data, while the analysis of big data makes it possible to trace the (digital) identity of each individual. In this complex scenario, the EU appears to be driven by the will to build an anthropocentric protection system. That is made possible through what is identified in the contribution as an equilateral triangle whose sides are cybersecurity, data protection, and AI regulation. After a brief examination of the current regulatory framework, the essay analyzes two case studies that illustrate the opportunities/criticalities inherent in the relationship between AI and personal identity. In conclusion, the question arises as to what the frontiers of the next AI regulatory framework might be.